Interaction of Person-Affect-Cognition-Execution (I-PACE) Model on Addictive Behavior - Embun Kumalaratih; Hendy Muagiri Margono (Jurnal Psikiatri Surabaya, 2023)
AbstractsIntroductions: Adiction is a pattern of substance abuse behavior characterized by overuse of the substance (compulsive use), the safety of its availability, and a high likelihood of relapse after discontinuation. There are 3 (three) stages of addiction, those are a stage of internal change, lifestyle change, and life breakdown. Objectives: This study aims to explore the I-PACE concepts about its components and their relation with the emergence of addictive usage of certain internet services including gaming, online gambling, pornography addiction, online shopping, and social networking. Methods: This study is a literature review that collects from various source of scientific journals related to the psychiatric management of the disorder. Several studies from the international database Pubmed Central including textbooks review papers, comments, and editorials are reviewed to evaluate I-PACE concepts concerning the components and their interaction with addictive behavior. Results: The findings show that the I-PACE model which includes the P component (person), the A component (affective), the C component (cognitive), and the E component (executive function) explains the disruption in a person’s decision-making. The anatomy of the frontostriatal circuit, notably between the ventral striatum, amygdala, and dorsolateral prefrontal area, is particularly significant for the early stages of the addictive process and the dorsal striatum for the latter stages. Conclusions: Interactions between components that occur in certain situations will result in addictive behavior due to the formation of satisfaction and compensation related to that behavior .